Cholecystectomy during esophagectomy is safe but unnecessary. Issue 1 (2nd January 2020) - Cavallin, Francesco; Scarpa, Marco; Cagol, Matteo; Alfieri, Rita; Ruol, Alberto; Chiarion Sileni, Vanna; Rugge, Massimo; Ancona, Ermanno; Castoro, Carlo
Abstract: Background: Prophylactic cholecystectomy has been proposed as a concomitant procedure during upper gastrointestinal surgery. This study evaluates the safety and the need of concurrent cholecystectomy during esophagectomy for cancer. Methods: All consecutive esophagectomies for esophageal cancer at the Center for Esophageal Diseases in Padova (Italy) between 1992 and 2011 were included. The safety of concurrent cholecystectomy was evaluated by surgical outcomes (length of stay, postoperative mortality and perioperative complications). The need for concurrent cholecystectomy was evaluated by occurrence of biliary duct stones and of cholelithiasis/cholecystitis after esophagectomy. Results: Cholecystectomy was performed during 67 out of 1087 esophagectomies (6.2%). Cirrhosis or chronic liver disease was associated with receiving cholecystectomy during esophagectomy (OR: 1.99, 95%C.I. 1.10–3.56). Patients receiving and those not receiving cholecystectomy showed similar length of stay (median 14 days, p = .87), postoperative mortality (3.0% vs. 2.5%, p = .68), intraoperative complication (4.5% vs. 7.1%, p = .62), early complications (52.2% vs. 44.6%, p = .25) and late complications (20.9% vs. 24.8%, p = .56). Cholelithiasis/cholecystitis after esophagectomy occurred in 61 (6.1%) patients, with only four requiring cholecystectomy during follow-up. The biliary stone occurrence was nil. Only pathologic stage III-IV (OR: 2.17, 95%C.I. 1.19–3.96) was associated with cholelithiasis/cholecystitis after esophagectomy. Conclusion: Routine prophylactic cholecystectomy during esophagectomy could be safe but unnecessary.